2021
DOI: 10.3390/biom11081193
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of Zinc-Finger Protein 433 as a Possible Prognostic Biomarker for Clear-Cell Renal Cell Carcinoma

Abstract: Clear-cell renal cell carcinoma (ccRCC) is the most common and aggressive form of all urological cancers, with poor prognosis and high mortality. At late stages, ccRCC is known to be mainly resistant to chemotherapy and radiotherapy. Therefore, it is urgent and necessary to identify biomarkers that can facilitate the early detection of ccRCC in patients. In this study, the levels of transcripts of ccRCC from The Cancer Genome Atlas (TCGA) dataset were used to identify prognostic biomarkers in this disease. Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…FGL1, fibrinogen-like protein 1, which is known as a novel potential immune checkpoint target [ 58 ], was recognized to be upregulated in tumor tissues and plasma specimens of ccRCC patients, and high FGL1 expression predicted a poor prognosis. In fact, there are many genes that have been identified as potential biomarkers in ccRCC, such as ZNF433 [ 59 ], AQP9 [ 60 ], SPINK13 [ 61 ], and DEF6 [ 62 ]. These works are different from each other for their interested and focused genes vary, but all genes identified are treasures for they have enhanced our understanding of ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…FGL1, fibrinogen-like protein 1, which is known as a novel potential immune checkpoint target [ 58 ], was recognized to be upregulated in tumor tissues and plasma specimens of ccRCC patients, and high FGL1 expression predicted a poor prognosis. In fact, there are many genes that have been identified as potential biomarkers in ccRCC, such as ZNF433 [ 59 ], AQP9 [ 60 ], SPINK13 [ 61 ], and DEF6 [ 62 ]. These works are different from each other for their interested and focused genes vary, but all genes identified are treasures for they have enhanced our understanding of ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Clusters of closely related ZFPs are located on chromosomes 4, 7, 8, 10, 19, with the largest clusters located on the p and q arms of chromosome 19 (6,(31)(32)(33)(34)(35). We recently reported that ZNF433, a KRAB-ZFP located within a cluster found at chr19p13.2, is down-regulated in ccRCC, and its expression is closely associated with clinicopathological features of ccRCC (19). Given that there are several related KRAB-ZFPs CANCER GENOMICS & PROTEOMICS 19: 305-327 (2022) in this region, we examined whether these proteins were also differentially expressed in clear cell renal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several large KRAB-ZFP clusters are located on chromosome 19 (chr19), and several studies have linked genetic alterations in chromosome 19p13 to cancers (12)(13)(14)(15)(16)(17)(18). Using data mining techniques, we recently identified ZNF433, a zinc finger that is differentially expressed in ccRCC (19) and that may be a biomarker for ccRCC. ZNF433 is part of a cluster of KRAB-ZFPs that are located on chromosome 19p13.2.…”
mentioning
confidence: 99%
“…Furthermore, transcriptome profiling of KRAB‐ZNF‐expressing renal cancer (RCC) revealed a variety of stem cell markers, including ZNF2, ZNF256, ZNF585, and ZNF829, and they may act as prognosis predictors 104 . Additionally, ZNF433 is highly methylated in clear‐cell renal cell carcinoma (ccRCC), along with significantly decreased expression and mutations of BAP1, SETD2, and KDM5C genes, which are associated with metastasis 105 . As a consequence, ZNFs can be a prognostic marker in urinary‐related cancers.…”
Section: Role Of Znfs In Different Tumorsmentioning
confidence: 99%
“…104 Additionally, ZNF433 is highly methylated in clear-cell renal cell carcinoma (ccRCC), along with significantly decreased expression and mutations of BAP1, SETD2, and KDM5C genes, which are associated with metastasis. 105 As a consequence, ZNFs can be a prognostic marker in urinary-related cancers.…”
Section: Other Cancersmentioning
confidence: 99%